On the axioms of quadratic form schemes - Pękała, Jan. G. (Annales Mathematicae Silesianae, 1990)
We show that the generally accepted axioms C1, C2 and C3 of quadratic form schemes can be replaced by two simply axioms S1 and S2. Several operations on schemes and the notion of a complete scheme are introduced in the paper. A proof is given that every elementary scheme is complete.